Enhancing social and linguistic skills in children with autism: A semi‐randomized controlled clinical trial of a virtual reality‐based communicative rehabilitation programme - Hassnaa O. Mohammed; Ehab M. Eid; Enas Rady Younes (Journal of Neuropsychology, 2026)
Abstract Autism spectrum disorder (ASD) is characterized by persistent deficits in social communication, and conventional therapies often struggle to facilitate the generalization of these skills to real‐world settings. This study aimed to determine the effectiveness of a virtual reality (VR)‐based communication rehabilitation intervention as a supplement to conventional treatment for improving the linguistic and social communication skills of Arabic‐speaking Egyptian children with ASD. A clinical trial with a pretest–posttest control group design was employed, wherein 60 children aged 4–6 years with mild to moderate ASD were assigned to either VR plus conventional therapy (Group I, n = 30) or conventional therapy alone (Group II, n = 30). Over 6 months, participants received 2 weekly 30‐min sessions. Outcomes were measured at baseline, immediately post‐intervention and at a 3‐month follow‐up using the Preschool Language Scale‐Fourth Edition, the Childhood Autism Rating Scale‐Second Edition and an ASD Social Skills Scale. Group I demonstrated statistically significant improvements in receptive and expressive language ages ( p < .001) and total social skills scores ( p < .001) compared to Group II. Crucially, these therapeutic gains were sustained at the 3‐month follow‐up with no significant deterioration ( p > .05). VR‐based communication rehabilitation is a highly effective and sustainable intervention for supplementing language and social skills in young children with ASD. Its integration into clinical practice provides a scalable, engaging and culturally adaptable platform for neurodevelopmental care.